Hybrid Authority Management of Nasab-Based Religious Leadership among the Habaib in Indonesia: Tradition, Modernity, and Digital Transformation - Jamaludin, Muhamad; Sa'idah, Nur; Firdaus; Malik, Muhammad Hisyam (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
This study critically examines the management strategies of nasab-based religious authority among the Habaib in Indonesia, emphasizing the hybridity between traditional and modern forms of leadership. Utilizing a qualitative systematic literature review guided by the PRISMA framework, combined with Critical Discourse Analysis, the research analyzes 25 key scholarly articles alongside empirical digital media content and field observations. Grounded in Max Weber’s typology of authority, the findings reveal that lineage from the Prophet Muhammad serves as a foundational source of charismatic legitimacy for the Habaib, which is actively maintained through religious symbolism, public narratives, and social engagement. The study highlights a strategic adaptation to digital media platforms, enabling the Habaib to expand their influence beyond conventional institutions and engage younger, urban Muslim audiences. This digital hybridity complements institutional participation in formal religious and political spheres, fostering a dual legitimacy that navigates the tensions between tradition and modernity. The implications underscore the significance of hybrid authority models in sustaining religious leadership amid sociocultural modernization and digital transformation in Muslim-majority societies. Limitations include geographic concentration on Java and Sumatra and focus on social media-active groups. Recommendations for future research advocate broader, comparative investigations of nasab-based authority and its impact on religious pluralism and community cohesion